Vaccination-infection interval determines cross-neutralization potency to SARS-CoV-2 Omicron after breakthrough infection by other variants - Miyamoto, Sho; Arashiro, Takeshi; Adachi, Yu; Moriyama, Saya; Kinoshita, Hitomi; Kanno, Takayuki; Saito, Shinji; Katano, Harutaka; Iida, Shun; Ainai, Akira; Kotaki, Ryutaro; Yamada, Souichi; et al. (Med (New York, N.Y. : Online), 2022)
The immune profile against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has dramatically diversified due to a complex combination of exposure to vaccines and infection by various lineages/variants, likely generating a heterogeneity in protective immunity in a given population. To further complicate this, the Omicron variant, with numerous spike mutations, has emerged. These circumstances have created the need to assess the potential of immune evasion by Omicron in individuals with various immune histories. The neutralization susceptibility of the variants, including Omicron and their ancestors, was comparably assessed using a panel of plasma/serum derived from individuals with divergent immune histories. Blood samples were collected from either mRNA vaccinees or from those who suffered from breakthrough infections of Alpha/Delta with multiple time intervals following vaccination. Omicron was highly resistant to neutralization in fully vaccinated individuals without a history of breakthrough infections. In contrast, robust cross-neutralization against Omicron was induced in vaccinees that experienced breakthrough infections. The time interval between vaccination and infection, rather than the variant types of infection, was significantly correlated with the magnitude and potency of Omicron-neutralizing antibodies. Immune histories with breakthrough infections can overcome the resistance to infection by Omicron, with the vaccination-infection interval being the key determinant of the magnitude and breadth of neutralization. The diverse exposure history in each individual warrants a tailored and cautious approach to understanding population immunity against Omicron and future variants. This study was supported by grants from the Japan Agency for Medical Research and Development (AMED). [Display omitted] •Omicron is resistant to neutralization by mRNA-vaccinated, infection-naïve sera•Omicron is cross-neutralized by mRNA-vaccinated sera with breakthrough infection•Vaccination-infection interval correlates with cross-neutralization activity The immune profile against SARS-CoV-2 has dramatically diversified due to a complex combination of exposure to various vaccines and infection by various variants. These circumstances created the need to assess the potential of “immune escape” by Omicron in individuals with various immune histories. In this study, the authors found that individuals who experienced breakthrough infection (i.e., were vaccinated and then infected) with Alpha or Delta showed much higher level of antibodies against Omicron compared with individuals who were vaccinated but never infected. Also, the time interval between vaccination and breakthrough infection strongly correlated with the level of antibodies against several variants. These results show the need for a tailored approach in understanding immunity against Omicron and future variants at individual and populational levels. Miyamoto et al. report that sera from COVID-19 mRNA vaccine breakthrough cases due to Alpha or Delta infection demonstrated improved cross-neutralization against the Omicron variant, and the time interval between vaccination and breakthrough infection was a key determinant of the magnitude and breadth of neutralizing activity against several variants.